Stimulasi, Deteksi dan Intervensi Dini Orang Tua terhadap Pencegahan Penyimpangan Pertumbuhan dan Perkembangan Anak Balita - Inna Sholicha Fitriani; Rona Riasma Oktobriariani (Universitas Muhammadiyah Ponorogo, 2017)
Healthy, intelligent, attractive, and good moral children is the desire of every parent. There are many children undergo growth delays that can be caused by a lack of parents caring in stimulating growth, early detection or early intervention. The method used in this study was exploratory qualitative research design presented in descriptive analytic. Data analysis technique used were data collection and categorization of data reduction, draw conclusions verification and presentation of data. The results showed that stimulation of the parents to their children was 51.1% or 23 respondents. Early detection of children development irregularities with the greatest frequency was the respondents who did early detection with the result of 55.6 % as 25 respondents. Early intervention against deviations growth of children with the greatest frequency was the respondents who did not intervene early in children under five against irregularities with results of 71.1% or 32 respondents